Collaborative dialogue between complete beginners of Chinese as a foreign language: implications it has for Chinese language teaching and learning. Issue 4 (3rd July 2020) - Bao, Rui
ABSTRACT: Collaborative dialogue has been seen as an important aspect of L2 learning. However, the extent to which collaborative dialogue contributes to learning depends very much on the context in which it takes place. Informed by a sociocultural perspective of learning, this study investigated the nature of the collaborative dialogue between complete beginners of Chinese as a foreign language (CFL) when engaging in task completion. Data were analysed by focusing on the occurrences, linguistic focuses, sources and resolutions of language-related episodes (LREs). Results indicated that beginners of CFL produced a large number of LREs, most of which focused on forms and were correctly resolved. However, variations in these LREs were also identified among learner pairs. It is suggested that beginners of CFL benefited from their collaborative dialogue. Meanwhile, it was highlighted that this benefit might be affected by different contextual factors such as proficiency, task, pair dynamics and individual learner difference, especially the linguistic features of Chinese language in this case. Finally, implications for CFL teaching and learning are discussed.